USE OF COMPUTER FOR BLOOD TRANSFUSION BUSINESS IN HOSPITAL (2) A Present Status in Utilization of the Reference System of Patients' Transfusion Information - Ito, Kazuhiko; Yoshida, Hisahiro; Yamashita, Kimiko; Fukunaga, Keiko; Hirakawa, Akina; Tobe, Takayoshi (Journal of the Japan Society of Blood Transfusion, 1986)
A present status of utilizing the reference system of patients' transfusion information during the 19 months from May 1, 1984 to Nov. 30, 1985 was monitored in Kyoto University Hospital. The reference frequency was 6411 in the Blood Transfusion Service and 476 in the polyclinic divisions, and was approximately constant in the former but high in June and July in the latter. The results of the transfusion examination and the transfusion histories of patients were the reference items with almost equal frequency in the Blood Transfusion Service but the latter was the major one in the polyclinic dividions. A high significant correlation (r=0.87) was observed between the reference frequency and the supplied units of the blood preparations in each clinic division. To clarify the reason of the low reference frequency in the polyclinic division, the doctors' opinions about the reference system were researched. Only 58% of the doctors had the license necessary for the reference and 41% of the doctors did not know about the reference system. Thus, the low reference frequency seems to be ascribed to the facts that PR for the doctors about the reference system is lacked, and that the rate of the doctors have the license for the reference is 58% and that the doctors in the clinical division were informed of the results of each transfusion examination by another transmission procedure.